Analysis of growth, nutrient uptake and production of three virus-free garlic cultivars - Hahn, Leandro; Feltrim, Anderson Luiz; Paviani, Angela Cristina; Valmorbida, Janice; Wamser, Anderson Fernando; Werner, Simone Silmara (Comunicata Scientiae, 2025)
Garlic cultivars in southern Brazil are virus-free, however, the rate of nutrient absorption and plant growth is unknown. The objective of this work was to determine the growth curve, production and nutrient uptake of three virus-free garlic cultivars. The experiment was conducted in Fraiburgo, SC state, in a randomized complete block design, with four replicates. The treatments were arranjed in a factorial 3 x 10 scheme with parcel subdivided in time. The three cultivars (Ito, Caçador and Quitéria) were distributed in the parcels and ten collects (14, 28, 42, 56, 70, 84, 98, 112, 126 and 140 days after planting) were the subparcel. The plant height, number of leaves, leaf area and extraction of N, P, K, Ca, Mg, Zn, Fe and Cu were determined. The three cultivars present differences in their growth curve and accumulation of nutrients. Nutrient extraction and dry mass accumulation are highly intensified after the plants differentiation into cloves. The maximum accumulation of all nutrients and the bulbs and total dry mass of plants occur at harvest. The nutrients absorption follows the sequence: K>N>Ca>P>Mg>Fe>Zn>Cu.